Recent Advances in Pyrolysis - Al- Haj Ibrahim, Hassan (IntechOpen, 2020)
Pyrolysis is an irreversible thermochemical treatment process of materials at elevated temperatures in an inert atmosphere. It is basically a carbonisation process where an organic material is decomposed to produce a solid residue with high (or higher) carbon content and some volatile products. The decomposition reactions are accompanied in general with polymerisation and isomerisation reactions. The end products of pyrolysis can be controlled by optimizing pyrolysis parameters such as temperature and residence time. Pyrolysis is used heavily in the chemical industry to produce many forms of carbon and other chemicals from petroleum, coal, wood, oil shale, biomass or organic waste materials, and it is the basis of several methods for producing fuel from biomass. Pyrolysis also is the process of conversion of buried organic matter into fossil fuels.